Fast Photoresponse From 1T Tin Diselenide Atomic Layers - Yu, Peng (2016)
Atomically layered 2D crystals such as transitional metal dichalcogenides (TMDs) provide an enchanting landscape for optoelectronic applications due to their unique atomic structures. They have been most intensively studied with 2H phase for easy fabrication and manipulation. 1T phase material could possess better electrocatalytic and photocatalytic properties, while they are difficult to fabricate. Herein, for the first time, the atomically layered 1T phase tin diselenides (SnSe2, III-IV compound) are successfully exfoliated by the method of mechanical exfoliation from bulk single crystals, grown via the chemical vapor transport method without transport gas. More attractively, the high performance atomically layered SnSe2 photodetector has been first successfully fabricated, which displays a good responsivity of 0.5 A W−1 and a fast photoresponse down to ≈2 ms at room temperature, one of the fastest response times among all types of 2D photodetectors. It makes SnSe2 a promising candidate for high performance optoelectronic devices. Moreover, high performance bilayered SnSe2 field-effect transistors are also demonstrated with a mobility of ≈4 cm2 V−1 s−1 and an on/off ratio of 103 at room temperature. The results demonstrate that few layered 1T TMD materials are relatively stable in air and can be exploited for various electrical and optical applications.